Detailed polymorphism study on cytomegalovirus DNA polymerase gene to reveal the most suitable genomic targets for quantitative Real-time PCR - Bilenoglu, Onur; Altindis, Mustafa; Oz, Ersoy; Yucel-Oz, Yeliz; Irigul-Sonmez, Oyku; Unal, Can Bora (ASSOC BASIC MEDICAL SCI FEDERATION BOSNIA & HERZEGOVINA SARAJEVO, 2015)
The human cytomegalovirus (HCMV) is an important human pathogen primarily affecting immunocompromised patients, like transplant recipients or HIV-infected individuals. Early diagnosis of cytomegalovirus (CMV) infection in high-risk patients is essential in order to start preemptive treatments. pol (UL54) gene encoding for HCMV viral DNA polymerase is a well-defined target for HCMV detection in clinical samples and identifying most highly conserved regions for primer design remains crucial. Though real-time polymerase chain reaction (qPCR) is a rapid and sensitive method for HCMV detection, failure to detect some HCMV strains due to primer and target mismatches have led the researchers to explore more sensitive and reliable methods. Hence, to understand the broader diversity of the pol mutations in HCMV and to specify the most suitable region for primer-probe design to be used in qPCR assay, we studied both nucleotide and amino acid heterogeneities in 60 HCMV positive samples that were collected to represent national mutational prevalence of pol gene of HCMV in Turkey. The test was designed with a new set of primers-probe for HCMV detection and quantification based on the sequencing data which revealed the most conserved region on the pol gene. Statistical probit analysis was applied on qPCR studies which revealed a 95% detection limit of 100 copies/mL. In addition, linearity, reproducibility, and precision of the new test were assessed for diagnostic purposes.
Keywords: Cytomegalovirus; nucleotide variations; real-time polymerase chain reaction; pol gene; TRANSPLANT RECIPIENTS; IMMUNOCOMPROMISED PATIENTS; ANTIVIRAL DRUGS; RESISTANCE; GANCICLOVIR; RETINITIS; STRAINS; FOSCARNET; THERAPY; Research & Experimental Medicine